SISTEM PEMBERI PAKAN IKAN SECARA OTOMATIS BERBASIS MIKROKONTROLER ATMega8535 - Setyawan, Herry; Misto, Misto; Gumay, Rofy Fazra (Jurnal Fisika FLUX, 2013)
Abstract: An electronic system based on Atmega8535 microcontroller for food fishfeding has been done. The system was employed a RTC, a pair infrared LED andphotodiode sensor, DC motor, driver circuit, a microcontroller, and LCD display. Themicrocontroller was programmed with C language and AVR program that suitable forthe device. The system was supported by a RTC device to get the main time basesignal of the system time. All of the system was controlled by microcontroller. Thesignal from the microcontroller is send to LCD and fish food applicator. It was concludedthat the system work well well since the all parameter and action were displayed onmonitor simultaneously and the applicator.Keyword: ATMega8535, RTC, infrared LED and photodiode sensor, DC motor,applicator